Regulation and Sanctions Against Unfair Business Competition: Challenges in Law Enforcement - Polontoh, Herry; Saputri, Fitri Arianti (Jurnal Hukum dan Keadilan, 2025)
This study aims to examine the effectiveness of regulations and legal sanctions in overcoming unfair business competition practices and identify the main challenges in law enforcement in Indonesia. The method used is a normative legal research method, with a statute approach, a conceptual approach, and a case approach. The focus of the study is directed to the analysis of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and its implementing regulations, as well as its application in several decisions of the Business Competition Supervisory Commission (ICC). The results of the study show that in substance, the existing regulations are adequate to regulate and prohibit unfair business competition practices. However, implementation in the field still encounters a number of serious obstacles, such as the limited authority of ICC, difficulties in proving in practice, and weak legal awareness among business actors. Therefore, legal reforms are needed aimed at strengthening ICC's institutions, simplifying legal procedures, and imposing stricter sanctions to create a deterrent effect. In addition, sustainable political commitment and public education are also needed as part of a long-term strategy to create a healthy, fair, and competitive business competition climate in Indonesia